Pembuatan tool pemodelan eksperimen bandul matematis dengan pengontrolan panjang tali otomatis untuk analisis video tracker (Mathematical pendulum experiment modeling tool fabrication with automatic rope length control for video tracker analysis) - - Yani; - Asrizal (Department of Physics – Universitas Negeri Padang UNP, 2019)
Physics is an interesting science in the world. The reason is that physics is able to explain physical phenomena and phenomena that occur in the world. One of the phenomena in physics is the simple harmonic motion of the mathematical pendulum. Physical phenomena can be observed through experiments using research instruments. The observation results were indicated there that the pendulum mathematical experimental data was only limited to the oscillation time and the number of swings. In addition, the instruments used today have limitations in mathematical pendulum experiments. One solution to solve this problem is to use a mathematical pendulum experimental modeling tool with automatic string length control. This research aims to determine the accuracy and accuracy of string length control, determine the performance specifications of mathematical pendulum modeling tool performance, determine the accuracy and accuracy of mathematical pendulum experiment modeling tools, and determine the effect of string length changes on the mathematical pendulum modeling tool. This research was a type of engineering research which is a non-routine design activity, so that there are new contributions, both in the form of processes and products. Data collection were done in two ways, namely direct and indirect measurement. Direct measurement was done by varying the length of the rope in the mathematical pendulum experiment modeling tool. Indirect measurement to determine the accuracy and accuracy of the mathematical pendulum experiment modeling tool. Data were analyzed with descriptive statistics in the form of tables and graphs. Based on data analysis four research results can be stated. First, the average accuracy of controlling rope length is 99.40% with an average error percentage of 0.59%. The average accuracy is obtained by 99,81% with an average error of 0,70%. Second, the performance of the mathematical pendulum modeling modeling tool is a mathematical pendulum modeling modeling tool measuring 1.0 x 0.7 m with controlling the length of the rope using a stepper motor. Third, the average accuracy of the pendulum mathematical experimental modeling tool is 95.09% with an average error of 4.90%. The average of the pendulum mathematical experimental modeling tool is 98.60% with an average error of 1.40%. Fourth, the longer the rope used the greater the period obtained, it is inversely proportional to the smaller frequency. Meanwhile, the average acceleration of gravity is obtained at 9.95 m/s2 with an average error of 1.50%.